2009
DOI: 10.1186/1471-230x-9-68
|View full text |Cite
|
Sign up to set email alerts
|

Mapping of HNF4α target genes in intestinal epithelial cells

Abstract: BackgroundThe role of HNF4α has been extensively studied in hepatocytes and pancreatic β-cells, and HNF4α is also regarded as a key regulator of intestinal epithelial cell differentiation. The aim of the present work is to identify novel HNF4α target genes in the human intestinal epithelial cells in order to elucidate the role of HNF4α in the intestinal differentiation progress.MethodsWe have performed a ChIP-chip analysis of the human intestinal cell line Caco-2 in order to make a genome-wide identification o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
61
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 65 publications
(65 citation statements)
references
References 65 publications
4
61
0
Order By: Relevance
“…The literature examination revealed HNF4␣ capacity to bind to promoters of many genes involved in lipid metabolism, glutathione metabolism, oxidative stress, inflammatory processes, and transcription factor status (47)(48)(49). Because our study reveals potential HNF4␣ target genes that have not been previously identified in the literature (e.g.…”
Section: Microsomal Triglyceride Transfer Protein Enzymatic Activity-mentioning
confidence: 84%
“…The literature examination revealed HNF4␣ capacity to bind to promoters of many genes involved in lipid metabolism, glutathione metabolism, oxidative stress, inflammatory processes, and transcription factor status (47)(48)(49). Because our study reveals potential HNF4␣ target genes that have not been previously identified in the literature (e.g.…”
Section: Microsomal Triglyceride Transfer Protein Enzymatic Activity-mentioning
confidence: 84%
“…Cell Cultures and Transfections-The cells were grown, and reporter gene transfections were carried out as described in Boyd et al (12). The cells were stably transfected with SureSilencing TM shRNA plasmid for Human CDX2 (SABiosciences Corp.) according to the manufacturer's recommendations.…”
Section: Methodsmentioning
confidence: 99%
“…ChIP qPCR Analysis-Verification of enrichment due to immunoprecipitation was done as previously described (12). The primers listed in supplemental Data S1 were used to amplify human genomic sequences at CDX2-target loci.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations